Sacroiliac tuberculosis masquerading as mechanical lower back pain in a collegiate basketball athlete: a case presentation - Moyaert, M; Viljoen, J; Viviers, P; Derman, W; de Villiers, R (South African Journal of Sports Medicine, 2018)
Background:Sacroiliac tuberculosis is a rare condition for which early diagnosis and effective management frequently proves challenging. This report describes a case that was initially overlooked due to its presentation and unreported constitutional symptoms. Aim:To alert clinicians about skeletal tuberculosis, an often neglected diagnostic differential, which requires a high index of clinical suspicion, especially for patients from endemic areas. Findings:This patient’s presentation (sports injury) and unreported constitutional symptoms resulted in a delay in the diagnosis and initial institution of treatment. Implications:This report illustrates the importance of specifically asking about constitutional symptoms, even in sports injury settings and being mindful of infectious diseases or other chronic medical conditions, which may masquerade as common sports injuries.